2013
DOI: 10.1161/hypertensionaha.112.203547
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lower Body Positive Pressure on Upper Airway Cross-Sectional Area in Drug-Resistant Hypertension

Abstract: Abstract-We previously showed that in hypertensive patients the amount of fluid displaced from the legs overnight is directly related to the severity of obstructive sleep apnea and that the rostral fluid shift was greater in drug-resistant hypertensive patients. The findings suggested that this fluid redistribution increases upper airway collapsibility, yet more direct evidence is lacking. The present study examines the effects of graded lower body positive pressure on leg fluid volume, upper airway cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 32 publications
1
28
2
4
Order By: Relevance
“…Application of LBPP to healthy subjects and hypertensive patients decreased UA-XSA in association with an increase in neck circumference. 22,23 Furthermore, in the hypertensive patients the decrease in UA-XSA and increase in neck circumference were both directly related to the decrease in LFV. 23 In OSA patients, LBPP increased upper airway resistance in association with increased neck circumference.…”
Section: Fluid Shift and Sleep Apnea Variabilitymentioning
confidence: 86%
See 1 more Smart Citation
“…Application of LBPP to healthy subjects and hypertensive patients decreased UA-XSA in association with an increase in neck circumference. 22,23 Furthermore, in the hypertensive patients the decrease in UA-XSA and increase in neck circumference were both directly related to the decrease in LFV. 23 In OSA patients, LBPP increased upper airway resistance in association with increased neck circumference.…”
Section: Fluid Shift and Sleep Apnea Variabilitymentioning
confidence: 86%
“…22,23 Furthermore, in the hypertensive patients the decrease in UA-XSA and increase in neck circumference were both directly related to the decrease in LFV. 23 In OSA patients, LBPP increased upper airway resistance in association with increased neck circumference. 24 Finally, in healthy subjects, LBPP increased upper airway collapsibility in proportion to the decrease in LFV and the increase in neck circumference.…”
Section: Fluid Shift and Sleep Apnea Variabilitymentioning
confidence: 86%
“…19 We, therefore, considered the impact of substituting neck size for BMI in the multivariable model to examine for superiority of fit. We noted changes in model coefficients and significance and compared model fit using Akaike Information Criteria (AIC) with a better fitting model defined as two or more units lower than the comparison model.…”
Section: Study Proceduresmentioning
confidence: 99%
“…[12][13][14][15] Additionally, increased sympathetic activity, changes in autonomic cardiovascular modulation, increased systemic inflammation and increased chemo reflex drive, and increased rostral edema contribute to increases in BP, including rises that are refractory to standard medication treatment. [16][17][18][19] Randomized clinical trials have demonstrated modest antihypertensive benefits of treatment of SDB with CPAP, with mild reductions in BP of 3 to 5 mm Hg 20,21 compared with more substantive reductions in RHTN, namely 7 to 10 mm Hg. 22 Notwithstanding the vast interventional trial data published on SDB and HTN, relatively fewer randomized studies [23][24][25] have investigated the effect of CPAP on control of BP in patients with OSA and RHTN, and none have examined the effect of CPAP in real-world clinical practice settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation